MANAJEMEN USAHA SALON KECANTIKAN DI KECAMATAN PAYAKUMBUH BARAT - Nildawati, Nildawati; Rahmiati, Rahmiati; Astuti, Murni (Journal of Home Economics and Tourism, 2016)
This study aims to reveal beauty salon business management application based management functions including planning, organizing, implementation, and controlling the existing beauty salon business Payakumbuh city of West Sumatra. The research approach is DeskriptifKuantitatif. The population is all employees and business leaders from 10 Salons in Payakumbuh totaling 52 orang.Data taken using Guttman and Likert scale questionnaire, data analysis using techniques percentage of respondents attainment levels. The results showed that (1) The average percentage is 66.00% in medium categories, with a description of 92.50% to places of business planning, licensing / business legality 53.30%, 26.66% workforce planning, planning salon services beauty 95%, planning marketing / promotion 63.33%. (2) The average percentage indicator Organizing with an average percentage of 45.66% very poor category with a description of the organization of the division of tasks and coordination of efforts 23.33% 69.07%. (3) Implementation indicators with an average percentage of 68 % category was the description hairstyling services 71.81% and skin beauty services implementation procedures 64.04%. (4) Indicators monitoring (controlling) deangn average percentage of 67.5% being categorized with a description supervision planning tools and materials 72% and 63% of process control work. Based on the research results suggested that the beauty salon business actually implement the management function in run the business in order to provide good services to achieve business progress.Kata kunci: Manajemen, Usaha salon Kecantikan